The latest trends in the treatment of patients with depression - Otroshchenko, Nataliia (Psychosomatic Medicine and General Practice, 2025)
Introduction. All over the world, the number of patients with depression has recently increased significantly, in particular, caused by global upheavals. This disorder is characterized by a long course, frequent exacerbations and relapses, therapeutic resistance, suicidal danger, etc. Suffering of patients with depressive disorders (DD), lack of effectiveness of standard treatment methods, rising costs of medical services, tangible losses to society and countries motivate specialists to search for new treatment methods. Medical cannabis (MC), virtual reality (VR), the game of Tetris (GT), digital tools of social messengers (DTSM), brain-computer interface (BCI), which effectively affect the reduction of DD, relieve suffering and improve the quality of life of these patients, have recently attracted attention among the promising brands of treatment for patients with post-stress depression. Purpose. To analyze modern scientific sources regarding the prospects of improving medical and psychiatric care for patients with depression in the treatment of MK, VR, GT, DTSM, BCI. Methods. An analytical study of modern foreign and domestic literature on optimizing the treatment of patients with depressive disorders using MK, VR, GT, DTSM and BCI from scientific databases PubMed, Google Scholar, Web of Science, Scopus using methods of systematization and generalization was conducted. The results. The review analyzed the modern scientific literature, mainly for the last five years, on the available possibilities of treating patients with DR with MK, VR, GT, DTSM, BCI drugs, taking into account the peculiarities of the formation of depression in response to the distress of war. The effectiveness of these methods has been proven by foreign and domestic specialists based on the results of literature reviews, randomized studies, retrospective studies, patient surveys, which testify to a significant relief of symptoms of depression, anxiety, reduction of tension, improvement of sleep, etc. Traditional therapy is not always effective, it is characterized by side effects and pharmacoresistance, however, modern studies show a positive therapeutic effect and the prospects of using MK, VR, GT, DTSM, BCI in the treatment of patients with depression, provided that quality evidence studies are continued. Conclusions. The conducted research confirms the significant prevalence of depression caused by stress, the limited effectiveness of standard methods of treatment for patients with the specified disorder, the need for further study of the latest safe methods of treatment, in particular MK, VR, GT, CISM, BCI, and conducting qualitative evidence-based research in order to improve the effectiveness of medical and psychiatric care for patients with DD in the conditions of modern challenges.